Improving L2 Oral Accuracy and Grammatical Range Through Self-Assessment of Video Speech Drafts - Martin Javier Caicedo Pereira; Jhonny Alexander Lozano Bermúdez; Luis Alfonso Vanegas Medina (Universidad Nacional de Colombia, 2018)
This action research study examines the effect of self-evaluation on grammatical range and grammar accuracy on the English speaking performance of 27 foreign language university and pre-university students enrolled in three different language centers, in three different cities in Colombia. Participants were asked to record themselves answering different IELTS-type tasks for four times during a 6-week period and score and reflect towards their performance using IELTS-type analytical scoring rubrics and journals. Researchers used journals to register impressions, thoughts, and judgments observed during the process. The findings led to conclude that learners highly benefit from applying self-assessment techniques using videos of their production and a language benchmark to compare with in the improvement of their oral language accuracy and grammatical range.